2014
DOI: 10.5851/kosfa.2014.34.4.482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Repeated Freeze-Thaw Cycles on Beef Quality and Safety

Abstract: The objectives of this study were to know the effect of repeated freeze-thaw cycles of beef on the sensory, physicochemical quality and microbiological assessment. The effects of three successive freeze-thaw cycles on beef forelimb were investigated comparing with unfrozen fresh beef for 75 d by keeping at −20±1℃. The freeze-thaw cycles were subjected to three thawing methods and carried out to know the best one. As the number of freeze-thaw cycles increased color and odor declined significantly before cook wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 49 publications
9
13
0
Order By: Relevance
“…Drip loss in all treatments showed a significant ( p <0.01) change over the course of trial. The result of the current study agreed to Ambrosiadis et al (1994) and Rahman et al (2014) reported that rapid thawing of meat by submergence in water decreased the drip loss and in case of refrigerated thawing (28 h), which resulted in the highest drip loss. In another study up to 18.27% drip loss is observed by freeze-thawing pork ( Xia et al , 2009 ) which is similar to the result of this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Drip loss in all treatments showed a significant ( p <0.01) change over the course of trial. The result of the current study agreed to Ambrosiadis et al (1994) and Rahman et al (2014) reported that rapid thawing of meat by submergence in water decreased the drip loss and in case of refrigerated thawing (28 h), which resulted in the highest drip loss. In another study up to 18.27% drip loss is observed by freeze-thawing pork ( Xia et al , 2009 ) which is similar to the result of this study.…”
Section: Discussionsupporting
confidence: 92%
“…From other reports it is found that the optimal temperature for freezing meat is to be −40℃, as only a minimum amount of water is unfrozen at this point ( Estévez, 2011 ; Leygonie et al , 2012a ). Thawing of meat at commercial and domestic level in refrigeration temperature (4℃) ( Eastridge and Bowker, 2011 ), temperatures ranging from room temperature to 49℃ or microwave (Chemat et al , 2011) and running tap water ( Rahman et al , 2014 ) is being practiced for long since. The most commonly used determinants to measure the degree of lipid oxidation of beef are free fatty acids (FFA), peroxide value (POV), and thiobarbituric acid reactive substance (TBARS) values.…”
Section: Introductionmentioning
confidence: 99%
“…But in the result, it has been seen that the fresh lamb sample showed the greater value of weight loss percentage. There were no significant interactive effects found on thaw loss in different fresh and a frozen sample which was similar to the experiments done by Rahman et al (2014). The possible explanation of the greater value for fresh samples is that the fresh samples were not properly fresh and those were also kept in the frozen condition before the experiments.…”
Section: Shrinkage and Weight Loss Measurementsupporting
confidence: 82%
“…A study on the various hair and wool sheep and their crosses reported that genotype had an effect on cholesterol levels ranging from 50 to 250 mg 100 g −1 fresh meat (Bunch et al, 2004). Another study reported that cholesterol contents of the LD muscle were 63.0 and 63.3 mg 100 g −1 fresh meat for Île de France × Pagliarola and Gentile Di Puglia × Sopravissana while corresponding values for semimembranosus muscle were 75.3 and 67.1 mg 100 g −1 fresh meat, respectively (Salvatori et al, 2004). Previous studies reported that breed is the most important factor regarding the cholesterol content of lamb meat, independently of slaughter weight (Matthes et al, 1998;Nurnberg et al, 1998;Arsenos et al, 2000).…”
Section: Discussionmentioning
confidence: 99%